2014
DOI: 10.1371/journal.pone.0086196
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Bacteria Chlamydia Hijack Peroxisomes and Utilize Their Enzymatic Capacity to Produce Bacteria-Specific Phospholipids

Abstract: Chlamydia trachomatis is an obligate intracellular pathogen responsible for loss of eyesight through trachoma and for millions of cases annually of sexually transmitted diseases. The bacteria develop within a membrane-bounded inclusion. They lack enzymes for several biosynthetic pathways, including those to make some phospholipids, and exploit their host to compensate. Three-dimensional fluorescence microscopy demonstrates that small organelles of the host, peroxisomes, are translocated into the Chlamydia incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…Previous reports have shown that there are lipid droplets and peroxisomes within the inclusion lumen, suggesting the ability of inclusions to 'ingest' host organelles (Bastidas et al, 2013;Boncompain et al, 2014). Ultra-structurally, we recognized intrainclusion membranes and small vesicles dually labelled with Rab39a and CD63, probably delivered by fusion with MVBs ( Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Previous reports have shown that there are lipid droplets and peroxisomes within the inclusion lumen, suggesting the ability of inclusions to 'ingest' host organelles (Bastidas et al, 2013;Boncompain et al, 2014). Ultra-structurally, we recognized intrainclusion membranes and small vesicles dually labelled with Rab39a and CD63, probably delivered by fusion with MVBs ( Fig.…”
Section: Discussionsupporting
confidence: 52%
“…A lesser-understood phenomenon that also occurs and for which evidence has only recently begun to accumulate is the transport of entire vesicles into pathogen-occupied vacuoles (POVs) in the absence of membrane fusion. Indeed, intact lipid droplets, peroxisomes, multivesicular bodies and endoplasmic reticulum-derived vesicles are delivered into the C. trachomatis inclusion (Beatty, 2006; Cocchiaro et al ., 2008; Dumoux et al ., 2012; Boncompain et al ., 2014). Also, Rab14, which like Rab10 directs TGN exocytic traffic (Junutula et al ., 2004), was detected within the C. trachomatis inclusion (Capmany and Damiani, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However it requires dedicated equipment free of water due to immiscibility of different organic solvents with water, which would lead bad chromatographic performance, unstable baselines and other problems. Hydrophilic Interaction Liquid Chromatography (HILIC) is an interesting alternative approach using water miscible organic solvents for lipid class separation [6,7].…”
Section: Mass Spectrometry Based Methodsmentioning
confidence: 99%
“…The use of chromatographic separation enables resolving of isomers including cis/trans isomers [3]. In most cases, reversed phase (RP) separations using C8 or C18 columns with an Acetonitrile-iso-Propanol (ACN-iPrOH) gradient are employed [3][4][5], but also application of HILIC and normal phase separation is common [6,7]. Lipidomics is applied in any field of biological research ranging from cell cultures [8], microorganisms [9][10][11], plants [12,13] and mammals [14].…”
Section: Introductionmentioning
confidence: 99%